PENGELOLAAN KELAS DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SDN MEKARJAYA II KECAMATAN PURWASARI - Aisyah Apriliyanti; Masykur H. Mansyur; Jaenal Abidin (STAI Pelabuhan Ratu, 2023)
Classroom management is a teacher's effort in developing the learning process so that it runs creatively and directed. Classroom management is also important, because it can organize classes in a conducive, optimal and enjoyable manner, which will affect the success of learning and produce quality human resources. The purpose of this study was to determine classroom management by Islamic Religious Education (PAI) teachers at SDN Mekarjaya II Purwasari District. This study uses descriptive qualitative methods, with data collection techniques through observation, interviews and documentation. The results of this study indicate that in class management Islamic education teachers use various approaches that are adapted to the circumstances, the theme of the subject matter and the character of the students. In the learning environment, PAI teachers also manage classes systematically, including: regarding student management which includes organizing and assigning; management of classrooms including seating arrangement, class beauty, ventilation and light arrangements and arrangement of storage of goods; learning management includes the selection of learning methods and media; and managing student assessments or evaluations that focus on affective aspects. In addition, the teacher has also made all solutions to the obstacles encountered in class management, both from the conditions of students and teachers.